Aplikasi Pendeteksi Kemiringan Tiang Listrik - Abd. Jabbar, A.; Jabir, Haryanto; Pawelloi, A. Irmayani; Suwardoyo, Untung (Jurnal Sintaks Logika, 2025)
Electrical poles are components of low voltage and medium voltage overhead lines which have the main function of supporting electrical conductors. Monitoring the slope of electricity poles is important to maintain the safety and performance of the electricity network. The aim of this research is to create a tool to detect the tilt of electricity poles so that they remain in a safe position. Research with a qualitative methodology based on literature studies, using the MPU6050 sensor as a tilt detector and ESP32 as a microcontroller. The results of making this application can help state electricity employees (PLN) monitor the slope of electricity poles so they can find out the degree and status. The slope of the electricity pole is 00 - 100 with the status of the electricity pole being safe, 110 -200 degrees with alert status, 210 - 450 with emergency status